Pengaruh Board Diversity terhadap Manajemen Laba - Dewi Fatimah (Journal of Applied Accounting and Taxation, 2019)
This study examines the effect on board diversity against earning management. The used samples are non-financial companies listed on the Indonesia Stock Exchange from 2010 to 2013. The data collection method using a purposive sampling method and data used are panel data. The regression used is ordinary least squares regression (OLS) with a fixed-effect model approach and the random effect model. The results showed that board diversity proxied by gender, age, education, and tenure no significant effect on earnings management, whereas the diversity proxy board with tenure significant effect on earnings management. Earnings management using discretionary accruals proxy and use a proxy for board gender diversity, age, minority education, and tenure.